Research trends and hotspots of Colles fracture: a bibliometric analysis from 1980 to 2023 - Zhou, Chaoxi; Yu, Guangrong; Wang, Qinglei (Frontiers in Surgery, 2025)
BackgroundColles fractures, a common type of distal radius fracture, predominantly affect older adults and are often associated with osteoporosis. Understanding the epidemiology, treatment methods, and complications of Colles fractures is crucial for improving patient outcomes.ObjectiveThis bibliometric analysis aims to assess the trends, influential research, and collaboration patterns in Colles fracture studies from 1980 to 2023, providing insights into emerging areas of research.MethodsLiterature was retrieved from the Web of Science Core Collection (WoSCC), Science Citation Index Expanded (SCI-EXPANDED) using the search term “Colles fracture”. A total of 948 relevant documents, including 901 articles and 47 reviews, were analyzed. VOSviewer, CiteSpace, and bibliometrix were utilized for visualization and data analysis, focusing on publication trends and hotspots.ResultsThe analysis revealed a steady increase in publications and citation counts, peaking around 2010, with a notable decline in publication output post-2010 while citations continued to rise. The USA led in both publication volume and citation impact, with significant contributions from England, Canada, Germany, and Japan. Key authors such as Cooney WP and Jupiter JB were identified as influential, while the Journal of Hand Surgery-American Volume emerged as the leading publication outlet. Keyword analysis indicated a growing emphasis on epidemiology and outcomes research, reflecting broader public health concerns.ConclusionThis bibliometric analysis highlights the evolving research on Colles fractures from 1980 to 2023. Despite a plateau in publication rates, citations continue to increase, indicating the lasting influence of earlier studies. Significant advancements have been made in treatment methods, particularly in external fixation (EF) and open reduction internal fixation (ORIF). The growing interdisciplinary focus on Colles fractures, osteoporosis, and rehabilitation underscores the need for continued research to enhance clinical outcomes and preventive measures.